A Clinical Study of the Intra-Neuroendoscopic Technique for the Treatment of Subacute-Chronic and Chronic Septal Subdural Hematoma - Du, Bo; Xu, Jianzhong; Hu, Jintao; Zhong, Xianliang; Liang, Jian; Lei, Pengfei; Wang, Hao; Li, Weichun; Peng, Yuping; Shan, Aijun; Zhang, Yujuan (Frontiers in Neurology, 2020)
Objective The surgical technique, safety, efficacy and clinical application value of the intra-neuroendoscopic technique (INET) for the treatment of subacute-chronic and chronic septal subdural hematoma was investigated based on the structure and pathological features of the hematoma wall, and the critical factors of hematoma growth and recurrence were determined, in order to provide reference for clinical drug treatment. Methods A total of 94 patients who met the inclusion criteria were recruited between May 2015 and February 2019 and were divided into the INET treatment group (INET group, 45 cases) and the burr hole drainage (BHD) treatment group (control group, 49 cases). The hematoma fluid components and the morphological structure and pathological characteristics of the hematoma wall were analyzed, and the clinical and follow-up indicators between the two groups were compared. A multiple logistic regression model was established to analyze the risk factors associated with recurrence within 6 months. Results The D-dimer contents and the proinflammatory cytokine interleukin 6 (IL-6) in the hematoma were significantly higher than that of the peripheral venous blood(p=0.00).The hematoma recurrence rate within 6 months (4.4% vs. 24.5%, p=0.00) and the subdural drainage tube (SDT) placement duration ((2.1±0.6) d vs. (3.9±0.7) d, p=0.00) for the INET group were lower than those for the control group. The overall effective rate of the Bender grade at 1 month of follow-up did not differ significantly between the two groups (95.6% vs. 87.8%, p=0.32), but the proportion of patients who recovered to Bender grade 0 with no symptoms was significantly higher in the INET group than in the control group (86.7% vs. 67.3%, p=0.03). Multiple logistic regression analysis showed that INET surgery (odds ratio (OR) 3.71, 95% confidence interval (CI) 1.31-9.62, p=0.02), age of 65 years or younger (OR 1.51, 95% CI 1.05-2.87, p=0.03) and unilateral subdural hematoma (OR 1.76, 95% CI 1.05-3.41, p=0.02) were independent factors that reduced the postoperative recurrence rate. Conclusion The INET surgical plan based on the structure and pathological features of the subacute-chronic and chronic subdural hematoma wall can reduce the recurrence rate and improve the clinical prognosis.